Criminología del Sur - Carrington, Kerry; Hogg, Russell; Sozzo, Máximo; Guala, Natacha; Puyol, María Victoria (Universidad Nacional del Litoral, 2018)
Issues of vital criminological research and policy significance abound in the global South, with important implications for South/North relations and for global security and justice. Having a theoretical framework capable of appreciating the significance of this global dynamic will contribute to criminology being able to better understand the challenges of the present and the future. We employ southern theory in a reflexive (and not a reductive) way to elucidate the power relations embedded in the hierarchal production of criminological knowledge that privileges theories, assumptions and methods based largely on empirical specificities of the global North. Our purpose is not to dismiss the conceptual and empirical advances in criminology, but to more usefully decolonize and democratize the toolbox of available criminological concepts, theories and methods.As a way of illustrating how southern criminology might usefully contribute to better informed responses to global justice and security, this article examines three distinct projects that could be developed under such a rubric. These include, firstly, certain forms and patterns of crime specific to the global periphery; secondly, the distinctive patterns of gender and crime in the global south shaped by diverse cultural, social, religious and political factors and lastly the distinctive historical and contemporary penalities of the global south and their historical links with colonialism and empire building.